Potable Water from Industrial Wastewater (Chemical Engineering Research Bulletin, 2008)
The objective of the study was to treat the textile wastewater and convert it into potable grade water in the laboratory scale. It involved a rigorous treatment procedure involving screening, coagulation, flocculation, aeration, biological treatment, filtration and ion exchange. From the analysis of the treated water it can be saidÂ Â  that the industrial waste water can be converted into potable grade water. Keywords: Wastewater treatment, Zero discharge, Potable water. DOI = 10.3329/cerb.v12i0.1493 Chemical Engineering Research Bulletin 12 (2008) 20-23